تحقيق الفاعلية المنظمية من خالل تقنية المقارنة المرجعية دراسة تحليلية آلراء عينة من أعضاء الهيئة التدريسية في الجامعة اللبنانية والفرنسية - أ.م مظفر حمد علي; م.م. زانا مجيد صادق; م. سميرة علي ابراهيم (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study aims to achievement the organizational effectiveness by the technique benchmarking through a view of a sample of lecturer members at the Lebanese and French University in the city of Erbil, Kurdistan Region of Iraq. A survey questionnaire was designed and distributed to the sample study numbered (48) lecturers. 75 questionnaires distributed and (54) questionnaires returned. However, (48) questionnaires was suitable for analyzing. Two main hypotheses been building along with a number of subhypotheses and depended on the statistical analysis program SPSS to address the study problem. The most results that this study reached was there was a positive correlation as well as a strong impact between organizational effectiveness and the technique of benchmarking. Based on this result, this study presented a set of recommendation, such as the necessitate to depend on plans in a successful and fruitful manner to conduct Benchmarking operations through conducting inspections and constant comparison in a way that ensures organizations compete properly with other organizations.